Cardiomyocyte GTP Cyclohydrolase 1 Protects the Heart Against Diabetic Cardiomyopathy - Wu, Hsiang-En (Sci Rep, 2016)
Diabetic cardiomyopathy increases the risk of heart failure and death. At present, there are no effective approaches to preventing its development in the clinic. Here we report that reduction of cardiac GTP cyclohydrolase 1 (GCH1) degradation by genetic and pharmacological approaches protects the heart against diabetic cardiomyopathy. Diabetic cardiomyopathy was induced in C57BL/6 wild-type mice and transgenic mice with cardiomyocyte-specific overexpression of GCH1 with streptozotocin, and control animals were given citrate buffer. We found that diabetes-induced degradation of cardiac GCH1 proteins contributed to adverse cardiac remodeling and dysfunction in C57BL/6 mice, concomitant with decreases in tetrahydrobiopterin, dimeric and phosphorylated neuronal nitric oxide synthase, sarcoplasmic reticulum Ca(2+) handling proteins, intracellular [Ca(2+)](i), and sarcoplasmic reticulum Ca(2+) content and increases in phosphorylated p-38 mitogen-activated protein kinase and superoxide production. Interestingly, GCH-1 overexpression abrogated these detrimental effects of diabetes. Furthermore, we found that MG 132, an inhibitor for 26S proteasome, preserved cardiac GCH1 proteins and ameliorated cardiac remodeling and dysfunction during diabetes. This study deepens our understanding of impaired cardiac function in diabetes, identifies GCH1 as a modulator of cardiac remodeling and function, and reveals a new therapeutic target for diabetic cardiomyopathy.